An innovative approach to the assessment of mood disturbances in patients with acute coronary syndrome. (7th February 2023) - Gostoli, Sara; Buzzichelli, Sara; Guidi, Jenny; Sirri, Laura; Marzola, Enrica; Roncuzzi, Renzo; Abbate-Daga, Giovanni; Fava, Giovanni A.; Rafanelli, Chiara
Abstract: Background: The clinical value of the identification of mood disorders in patients with acute coronary syndrome (ACS) is well established. However, assessment based on DSM criteria presents some limitations. This study aimed to provide an innovative strategy for evaluating the spectrum of mood disturbances in ACS. Methods: A total of 288 patients with a first episode of ACS underwent interviews based on DSM-IV-TR criteria (major depressive disorder, minor depression, and dysthymia), Diagnostic Criteria for Psychosomatic Research-DCPR (demoralization and type A behavior), and the Clinical Interview for Depression-CID. Additional self-report inventories (psychological well-being and distress) were administered. A total of 100 consecutive patients who satisfied criteria for DSM-IV-TR depression or DCPR demoralization were enrolled in a randomized controlled trial on a sequential combination of cognitive-behavioral and well-being therapy (CBT/WBT) vs clinical management (CM) and reassessed up to 30-month post-intervention. Results: A total of 29.9% of patients showed a DSM-IV-TR depressive syndrome. Inclusion of demoralization and type A identified psychological distress in 58% of the sample. According to CID, reactivity to social environment, fatigue, depressed mood, and somatic anxiety were the most common symptoms. Somatic symptoms were significantly associated with DSM-IV-TR depression (fatigue and changes of appetite), whereas environmental reactivity with demoralization. Both depression and demoralization were associated with higher distress and lower well-being. Unlike CM, CBT/WBT was significantly associated with decrease of guilt, pessimism, fatigue, and early insomnia (CID). Conclusions: The findings indicate that standard psychiatric approach identifies only a narrow part of mood disturbances affecting ACS patients. A more articulated assessment unravels specific clinical configurations that may entail prognostic and therapeutic implications.